Common holdings and strategic manager compensation: The case of an asymmetric triopoly - Werner Neus; Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2018)
We study an asymmetric triopoly in a heterogeneous product market where quantity decisions are delegated to managers. The two biggest firms are commonly owned by shareholders such as index funds while the smallest firm is owned by independent shareholders. Under such a common holding owner structure, the owners have an incentive to coordinate when designing their manager compensation schemes. This coordination leads to a reallocation of production and induces a redistribution of pro profits. The trade volume in the market is reduced so that shareholder coordination is detrimental to consumer surplus as well as welfare.
urn:nbn:de:bsz:21-dspace-833809
Keywords: G32; L22; M52; 330; common holdings; index funds; shareholder coordination; manager compensation